Activation of Terminally Differentiated Human Monocytes/Macrophages by Dengue Virus: Productive Infection, Hierarchical Production of Innate Cytokines and Chemokines, and the Synergistic Effect of Lipopolysaccharide - Chen, Yun-Chi (American Society for Microbiology, 2002)
Dengue virus (DV) primarily infects blood monocytes (MO) and tissue macrophages (Mφ). We have shown in the present study that DV can productively infect primary human MO/Mφ regardless of the stage of cell differentiation. After DV infection, the in vitro-differentiated MO/Mφ secreted multiple innate cytokines and chemokines, including tumor necrosis factor alpha, alpha interferon (IFN-α), interleukin-1β (IL-1β), IL-8, IL-12, MIP-1α, and RANTES but not IL-6, IL-15, or nitric oxide. Secretion of these mediators was highlighted by distinct magnitude, onset, kinetics, duration, and induction potential. A chemokine-to-cytokine hierarchy was noted in the magnitude and induction potential of secretion, and a chemokine-to-cytokine-to-chemokine/Th1 cytokine cascade could be seen in the production kinetics. Furthermore, we found that terminally differentiated MO/Mφ cultured for more than 45 days could support productive DV infection and produce innate cytokines and chemokines, indicating that these mature cells were functionally competent in the context of a viral infection. In addition, DV replication in primary differentiated human MO/Mφ was enhanced and prolonged in the presence of lipopolysaccharide (LPS), and LPS-mediated synergistic production of IFN-α could be seen in DV-infected MO/Mφ. The secretion of innate cytokines and chemokines by differentiated MO/Mφ suggests that regional accumulation of these mediators may occur in various tissues to which DV has disseminated and may thus result in local inflammation. The LPS-mediated enhancement of virus replication and synergistic IFN-α production suggests that concurrent bacterial infection may modulate cytokine-mediated disease progression during DV infection.